Medical Ethics. - Stambler, Moses (., 1995)
Keywords: dept.pch; faculty_collection; sabbatical_report

Measurement of the proportion of free to total prostate-specific antigen improves diagnostic performance of prostate-specific antigen in the diagnostic gray zone of total prostate-specific antigen - Luderer, Albert A.; Chen, Ya-Ting; Soriano, Thomas F.; Kramp, William J.; Carlson, Grant D.; Cuny, Carol; Sharp, Thomas; Smith, William; Petteway, Jason; Brawer, Michael K.; Thiel, Robert (Urology, 1995)
Objectives: This study examined the clinical significance of non-complexed (free) prostate-specific antigen (PSA) in the differential diagnosis of prostate cancer with an emphasis on patients with total PSA values between 4.0 and 10.0 ng/mL (the diagnostic gray zone). Methods: Serum samples were obtained from three specimen banks. Patient samples consisted of 55 untreated historically confirmed primary cancer, 62 men with untreated benign prostatic disease histologically confirmed by 6 negative sextant biopsies, and 64 asymptomatic healthy male controls with normal digital rectal examinations and PSA values less than 4.0 ng/mL. All patients were between the ages of 50 and 75 years. Total PSA levels were determined using the PA immunoassay performed on the TOSOH AIA-1200 automated immunoassay instrument. Free PSA levels were determined using a monoclonal-polyclonal antibody sandwich radioimmunoassay. The proportion of free to total PSA was calculated by dividing the patient's free PSA value by the total PSA value. Results: When all subjects were included, both total PSA and the proportion of free to total PSA significantly differentiated between patients with prostate cancer and patients with benign histologic conditions (P< 0.0001). However, in men with total PSA values between 4.0 and 10.0 ng/mL, the proportion of free to total PSA significantly differentiated between patients with benign and malignant histologic conditions (P = 0.0004), whereas the total PSA did not (P = 0.13). Among this subgroup of patients, the analysis of sensitivity and specificity showed that the proportion of free to total PSA had a clearly higher specificity compared with that of the total PSA at the same level of sensitivity. Conclusions: Measurement of the free PSA level in a patient's serum and calculation of the proportion of free to total PSA enhances the ability to distinguish benign histologic conditions from cancer while retaining high sensitivity for detecting cancer in men who present with total PSA levels between 4.0 and 10.0 ng/mL. A large-scale population-based study is currently in progress to confirm this preliminary finding. © 1995.
207 citations (Crossref) [2023-10-31] Citation Key Alias: pop00002 tex.type: [object Object]
Keywords: Aged; Case-Control Studies; Chromatography; High Pressure Liquid; Comparative Study; Diagnosis; Differential; Human; Immunoassay; Male; Middle Age; Prostate-Specific Antigen; Prostatic Hyperplasia; Prostatic Neoplasms; ROC Curve; Radioimmunoassay; Reference Values; Sensitivity and Specificity; adult; article; cancer diagnosis; controlled study; dept.pch; diagnostic accuracy; differential diagnosis; early diagnosis; human; immunoassay; major clinical study; male; monoclonal antibody; polyclonal antibody; priority journal; prostate cancer; prostate specific antigen; tumor marker